2013
DOI: 10.1111/aor.12190
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Full‐Thickness Wound Healing Using Epigallocatechin‐3‐O‐Gallate/Poly (Lactic‐Co‐Glycolic Acid) Membrane as Temporary Wound Dressing

Abstract: Epigallocatechin-3-O-gallate (EGCG) is a major polyphenolic compound in green tea. It has been known that EGCG regulates the secretion of cytokines and the activation of skin cells during wound healing. In this study, various concentrations of EGCG were added to the electrospun membranes composed of poly (lactic-co-glycolic acid) (PLGA), and its healing effects on full-thickness wounds created in nude mice were investigated. The electrospun membranes containing 5 wt% EGCG (5EGCG/PLGA membrane) exhibited cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…This factor is recognized as the strongest contributor to angiogenesis (Kapoor, Howard, Hall, & Appleton, ). Kim et al () found that the membranes containing EGCG can accelerate wound healing by the proliferation of epithelial cells and the formation of new capillaries (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This factor is recognized as the strongest contributor to angiogenesis (Kapoor, Howard, Hall, & Appleton, ). Kim et al () found that the membranes containing EGCG can accelerate wound healing by the proliferation of epithelial cells and the formation of new capillaries (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…PLGA electrospun membranes containing Epigallocatechin‐3‐O‐gallate exhibited faster wound healing in full‐thickness wounds created in nude mice. The underlying mechanisms include enhanced cell infiltration, reepithelialization, and angiogenesis PLGA‐metformin electrospun nanofibrous membranes improved wound healing and reepithelialization in diabetic rats relative to the respective controls . The same group also reported that electrospun nanofibrous metformin‐loaded collagen/PLGA scaffold membranes were more hydrophilic than collagen/PLGA membranes and exhibited a greater water‐containing capacity.…”
Section: Poly(lactic‐co‐glycolic Acid)mentioning
confidence: 94%
“…Wound dressings play an important part in the treatment of DFUs, and different dressings are used depending on the stage and type of DFU, based on the extent of injury, patient condition and tissues involved [29,30]. Many dermal replacements can improve diabetic wound healing, such as hyaluronic acid/PLGA core/shell fibre matrices [31] and epigallocatechin-3-O-gallate/PLGA [32]. Previously, we showed that PLGA/CNC nanofiber membranes can act as dermal regeneration templates and have better cytocompatibility than do PLGA nanofiber membranes.…”
Section: Discussionmentioning
confidence: 99%